En contexto para una filosofía de la educación y una educación filosófica en América Latina (2022)
The article presents the philosophical foundations with which to construct a Latin American philosophy that underpins a project of philosophy of education from popular education. This is done from the examination of the philosophical reflection of Leopoldo Zea and Amado Osorio. To this end, it develops around the presumed existence of: (1) a Latin American philosophy, (2) Latin American philosophical thought, (3) a presumed agreement on philosophy, (4) a philosophy of education in Latin America, and (5) a philosophy of education as a stronghold of a philosophical education in Latin America. The text also concludes that a Latin American philosophy does not have to have as a condition its rupture with the thinking of ordinary man; it is only a matter of recognizing their vital problems to provide reflective clarity and act on them with answers, even inspiring for other peoples.